The Influence of the Halal Lifestyle on Muslim Investor Decisions in Indonesia's Islamic Stock Market - Nurina Saffanah; Rezky Ratnasari Taufan; Achdian Anggreny B Anggreny B; Elda Fira; Widya Reskyawati Aminuddin (Golden Ratio of Auditing Research, 2026)
This study examines the influence of the halal lifestyle on Muslim investors' decision-making in Indonesia's Islamic stock market. As the country with the largest Muslim population in the world, Indonesia has experienced increasing interest in Sharia-compliant financial products, reflecting the alignment between investment preferences and Islamic values. This research employs a quantitative approach, with data collected through an online questionnaire distributed to 202 Muslim investors who invest in Islamic-based securities. The variables analyzed include religiosity, attitude, morality, and social media engagement as indicators of the halal lifestyle. The results of the multiple linear regression analysis indicate that religiosity, attitude, morality, and social media engagement each have a positive, statistically significant effect on investor decision-making. These findings indicate that investment behavior is influenced not only by rational financial considerations but also by spiritual beliefs, ethical values, and exposure to information through digital platforms. This research contributes to behavioral finance theory by integrating Islamic values and digital influences into the analysis of investment behavior. Furthermore, the study highlights practical implications for policymakers and financial institutions to strengthen Islamic financial literacy and promote awareness of halal investment among Muslim communities.